(3OhQ EJaGbjI JMQjQ JLGQI GdNOeGJ GdOhdjI (B((3GdLGJS(B) (3aj QaY caGAI COGA GdNOeGJ GdeUQajI (B/s - (3eQGO, SGej CMeO eMeOs ((3GdbGgQI(B: s (3GdecJH GdYQHj ddeYGQa(B, s, 2005)
(3jVe GdGWGQ GdYGe ddOQGSI, fTCI GdLGJ hJWhQgG heHGOFgG, GdNOeGJ GdeUQajI hGdJRGeGJ eUQ aj GJaGbjI GdLGJSs
(3HjHdjhZQGajG(B: (3U(B.309s
Keywords: (3GdHfhcs; (3GdHfhc(B- (3GdMSGHGJ GdeUQajI s; (3eUQ(B- (3GdHfhc s